A new species and new distributional records of Haroldius Boucomont, 1914 (Coleoptera: Scarabaeidae: Scarabaeinae) from southern Africa - Daniel, Gimo M.; Strümpher, Werner P.; Snäll, Stanislav (Zootaxa, 2021)
Haroldius lyleae Daniel, Strümpher & Snäll, new species, is described and illustrated from South Africa. The new species can be easily distinguished from other species of the genus by its notable triangular clypeus lacking the distinctive mid-anterior indentation and denticles present in other Haroldius Boucomont, 1914 species. Monomorium albopilosum Emery, 1895 (Hymenoptera: Formicidae: Myrmicinae) is recorded as a possible ant host of the new species. Haroldius modestus (Janssens, 1953) is recorded from Zimbabwe for the first time, and Haroldius convexus (Philips & Scholtz, 2000) is now recorded from the North West and KwaZulu-Natal Provinces of South Africa as well.